2015
DOI: 10.5194/amt-8-2061-2015
|View full text |Cite
|
Sign up to set email alerts
|

Robust, spatially scanning, open-path TDLAS hygrometer using retro-reflective foils for fast tomographic 2-D water vapor concentration field measurements

Abstract: Abstract.We have developed a fast, spatially scanning direct tunable diode laser absorption spectrometer (dTDLAS) that combines four polygon-mirror based scanning units with low-cost retro-reflective foils. With this instrument, tomographic measurements of absolute 2-D water vapor concentration profiles are possible without any calibration using a reference gas.A spatial area of 0.8 m × 0.8 m was covered, which allows for application in soil physics, where greenhouse gas emission from certain soil structures s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Figure 2 summarizes some representative results from a number of sensor development and implementation studies in terms of detection limits and bandwidths. It compares species concentration measurements in a variety of combustion systems including laboratory environments [1,[16][17][18][19][20][21][22], shock tube studies [23][24][25][26][27][28], industry processes [29][30][31][32][33], and engines [34][35][36][37][38][39][40][41][42][43][44][45][46]. For the purpose of making a direct comparison between different studies, the reported absolute minimal detection limits for several commonly probed species in combustion, including CO, CO 2 , H 2 O, and C 2 H 2 , are plotted on the same diagram against detection bandwidths.…”
Section: Sensor Design Targets and Measurement Challengesmentioning
confidence: 99%
“…Figure 2 summarizes some representative results from a number of sensor development and implementation studies in terms of detection limits and bandwidths. It compares species concentration measurements in a variety of combustion systems including laboratory environments [1,[16][17][18][19][20][21][22], shock tube studies [23][24][25][26][27][28], industry processes [29][30][31][32][33], and engines [34][35][36][37][38][39][40][41][42][43][44][45][46]. For the purpose of making a direct comparison between different studies, the reported absolute minimal detection limits for several commonly probed species in combustion, including CO, CO 2 , H 2 O, and C 2 H 2 , are plotted on the same diagram against detection bandwidths.…”
Section: Sensor Design Targets and Measurement Challengesmentioning
confidence: 99%
“…The absorption signal intensity becomes an integrated value of the optical path. In this study, several optical paths are intersected to each other to form the analysis grid, reconstructing 2D temperature distribution by a CT method (Ma et al, 2008;Wang et al, 2010;Kasyutich et al, 2011;An et al, 2011;Deguchi et al, 2012;Deguchi et al, 2015;An et al, 2015;Cai, et al, 2015;Jatana, et al, 2015;McCann, et al, 2015;Seidel, et al, 2015;Stritzke, et al, 2015;Kamimoto et al, 2016). Figure 4 shows concept of analysis grids and laser beam paths.…”
Section: Theorymentioning
confidence: 99%
“…Recently, combination of computed tomography (CT) and TDLAS has been studied and applied for two-dimensional (2D) measurements of temperature and concentration in combustion processes. 1524 In past studies, H 2 O absorption spectra using narrow wavelength range scanning lasers were used for 2D temperature measurement. 2024 However, these lasers are not applicable for temperature measurement in high-pressure condition, such as 1.0–5.0 MPa.…”
Section: Introductionmentioning
confidence: 99%